2017
DOI: 10.1038/s41467-017-01377-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of Atlantic overturning circulation in the recent decline of Atlantic major hurricane frequency

Abstract: Observed Atlantic major hurricane frequency has exhibited pronounced multidecadal variability since the 1940s. However, the cause of this variability is debated. Using observations and a coupled earth system model (GFDL-ESM2G), here we show that the decline of the Atlantic major hurricane frequency during 2005–2015 is associated with a weakening of the Atlantic Meridional Overturning Circulation (AMOC) inferred from ocean observations. Directly observed North Atlantic sulfate aerosol optical depth has not incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 67 publications
9
87
2
Order By: Relevance
“…For both detrending methods, the observed AMOC fingerprint exhibits a similar dipole pattern with opposite signs in the SPNA and the Gulf Stream region (Figures a and e) and similar multidecadal variations (Figures b and f), as found in previous studies (Joyce & Zhang, ; Yan et al, , ; Zhang, , ; Zhang & Zhang, ). The low‐pass filtered observed AMOC fingerprint (Figures b and f) has significant ( p < 0.05) positive correlations with various observed AMV‐related indices (Figures a–e and k–o) and the observed MAI (Figures e and e), for both detrending methods.…”
Section: Relationship Between Amv and Amoc Fingerprintsupporting
confidence: 85%
“…For both detrending methods, the observed AMOC fingerprint exhibits a similar dipole pattern with opposite signs in the SPNA and the Gulf Stream region (Figures a and e) and similar multidecadal variations (Figures b and f), as found in previous studies (Joyce & Zhang, ; Yan et al, , ; Zhang, , ; Zhang & Zhang, ). The low‐pass filtered observed AMOC fingerprint (Figures b and f) has significant ( p < 0.05) positive correlations with various observed AMV‐related indices (Figures a–e and k–o) and the observed MAI (Figures e and e), for both detrending methods.…”
Section: Relationship Between Amv and Amoc Fingerprintsupporting
confidence: 85%
“…The directly observed AMOC at 26°N from the RAPID program exhibits a significant downward shift over the recent decade since 2004, which has been widely interpreted as arising from intrinsic decadal/multidecadal AMOC variability and a reversal from the previous AMOC strengthening (e.g., Jackson et al, ; Robson, Hodson, et al, ; Robson et al, ; Smeed et al, , ; Yan et al, , ). The total reduction of the directly observed AMOC at 26°N between 2004–2009 and 2009–2014 is 2.9 Sv and is statistically significant (Frajka‐Williams et al, ).…”
Section: Amoc‐amv Linkagementioning
confidence: 99%
“…Reviews of Geophysics Robson et al, 2016;Smeed et al, 2018;Yan et al, 2017). In a recent study, the high correlation between the observed AMV index (based on linearly detrended basin-averaged low-pass-filtered North Atlantic SST anomalies) and the simulated ensemble mean AMV index from a large ensemble of twentieth-century…”
Section: 1029/2019rg000644mentioning
confidence: 99%
“…These phenomena include synopticscale tropical waves (e.g., Thorncroft & Hodges, 2001), tropical intraseasonal variability (e.g., Maloney & Hartmann, 2000), interannual sea surface temperature (SST) variability (Chen & Lin, 2011), and Atlantic multidecadal variability involving the Atlantic meridional overturning circulation (e.g., Goldenberg et al, 2001;Gray, 1984;Yan et al, 2017). These phenomena include synopticscale tropical waves (e.g., Thorncroft & Hodges, 2001), tropical intraseasonal variability (e.g., Maloney & Hartmann, 2000), interannual sea surface temperature (SST) variability (Chen & Lin, 2011), and Atlantic multidecadal variability involving the Atlantic meridional overturning circulation (e.g., Goldenberg et al, 2001;Gray, 1984;Yan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%